Association between SLCO1B1 polymorphism distribution frequency and blood lipid level in Chinese adults. Issue 1 (2nd January 2021) - Mo, Q; Huang, S; Ma, J; Zhang, J; Su, R; Deng, Q
ABSTRACT: Background: The variation of serum lipid levels can be part-related to certain genes. One such gene, SLCO1B1, encodes a transporter that may have a role in lipid metabolism. We hypothesised that differences in certain SLCO1B1 genotypes are related to levels of serum lipids. Materials and methods: We recruited 636 subjects who were genotyped for SLCO1B1 variants *1a, *1b, *5 and *15. Routine liver function tests, renal function tests and routine lipid indices were measured by standard techniques. Results: The most frequent genotypes were *1b/*1b (29.3%), *1b/*15 (27.5%), *1a/*1b (21.1%), *1a/*15 and *1b/*5 (10.2%) and *1a/*1a (8.5%). There were significant differences in levels of triglycerides and HDL in the four SLCO1B1 genotypes *1a/*1a, *1b/*1b, *1a/*1b and *1b/*15 (all p < 0.05). Conclusion: The genotypes *1a/*1a and *1a/*1b indicate a high risk of cardiovascular disease, while the *1b/*1b group may have a relatively low risk. SLCO1B1 may be involved in the metabolism of triglycerides and HDL. We have provided a tool for identifying potentially high-risk groups that could be helpful for early diagnosis and prevention, individualized drug therapy and even gene therapy.